(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
A liquid chromatography-tandem mass spectrophotometric (LC–MS/MS) method was developed to quantify Edoxaban in rabbit plasma employing liquid liquid extraction with ethyl acetate. Developed method was validated for specificity, precision, accuracy, recovery, and stability characteristics. Chromatographic separation was achieved on Chromolith C18column (100 mm x 4.6 mm x 5 μm) with 70:30 ratio of methanol and 0.1% formic acid as an isocratic mobile phase with a flow rate of 0.80 mL/min. The developed LC-MS method was applied to assess pharmacokinetics parameters of edoxaban in healthy rabbits. Six Male albino rabbits weighing 2.0-2.5 Kg were randomly selected for the pharmacokinetic study. Blood samples (1-mL) were withdrawn from the marginal ear vein from 0 to 24 hours after administration (1.2 mg/kg). Plasma was separated by centrifugation and the plasma concentrations of edoxaban at various times were determined by LC-MS/MS. Pharmacokinetic parameters was calculated. Edoxaban showed Tmax of 2.0 and mean Cmax, AUC0®t and AUC0®a for Test formulation is 213.83 ± 10.46, 945.13 ± 24.32 and 986.135 ± 19.31, respectively. A highly specific, rugged, and rapid method with sufficiently low LLOQ was developed to analyze routine samples of single dose or multiple-dose pharmacokinetics with any marketing formulation of edoxaban.